2012
DOI: 10.1021/cm302342v
|View full text |Cite
|
Sign up to set email alerts
|

Sillen–Aurivillius Intergrowth Phases as Templates for Naturally Layered Multiferroics

Abstract: The ferroelectric Sillen-Aurivillius phase Bi 5 PbTi 3 O 14 Cl, a layered structure containing three-layer perovskite-type blocks, has been modified by substituting magnetic transition metal cations M 3+ = Cr 3+ , Mn 3+ or Fe 3+ for 1 3 of the Ti 4+ cations, accompanied by co-doping of Bi 3+ for Pb 2+ . The aim of the modification was to produce naturally-layered ferroelectromagnetic compounds. Rietveld refinements against high-temperature synchrotron X-ray powder diffraction data show that the resulting new c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…The single-crystal XRD on the platelet crystal revealed that a pseudo-merohedral twin is likely present with domains in the ab plane, in addition to the ferroelectric domains. We also report the growth of single crystal Bi 4 (n = 1, 2, 3, ...) constitutes a promising material platform not only for the photocatalysis but also for ferroelectric [24] or multiferroic properties [25]. We believe that the knowledge of single crystal growth obtained in this study on Bi 4 NbO 8 X can be applied to other Sillén-Aurivillius oxyhalide compounds.…”
Section: Discussionmentioning
confidence: 55%
“…The single-crystal XRD on the platelet crystal revealed that a pseudo-merohedral twin is likely present with domains in the ab plane, in addition to the ferroelectric domains. We also report the growth of single crystal Bi 4 (n = 1, 2, 3, ...) constitutes a promising material platform not only for the photocatalysis but also for ferroelectric [24] or multiferroic properties [25]. We believe that the knowledge of single crystal growth obtained in this study on Bi 4 NbO 8 X can be applied to other Sillén-Aurivillius oxyhalide compounds.…”
Section: Discussionmentioning
confidence: 55%
“…[6][7][8][9] In the last years, layered oxides have attracted continuously growing attention for being a promising playground for the design of new multiferroic materials. 10,11 The structure of the layered oxides is typically composed by an alternation of perovskite blocks and spacing layers having a different structure, e.g. rock salt 12 or fluorite 13 , thus forming a superstructure.…”
Section: Introductionmentioning
confidence: 99%
“…These structures can be designated as X m (m = 1 or 2 according to the number of anion sheets). 4 This already vast family, called Bipox (Bismuth perovskite oxyhalides), [11][12][13][14][15][16][17][18][19][20] comprise structures where the fluorite layers are separated alternatively by perovskite and halide layers as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%